Fe–FeOx nanoparticles encapsulated in N-doped carbon material: a facile catalyst for selective synthesis of quinazolines from alcohols in water. Issue 23 (25th October 2022) - Wang, Fei; Zhu, Fuying; Ren, Enxiang; Zhang, Qiang; Lu, Guo-Ping; Lin, Yamei
Abstract : A Fe–FeO x @NC catalyst with N-doped carbon encapsulated Fe–FeO x nanoparticles has excellent performance in the synthesis of quinazolines. Abstract : The development of efficient and green synthetic strategies for N-heterocycle synthesis has always been a research hotspot in organic synthesis. A facile one-pot iron-catalyzed synthesis of quinazolines from alcohols in water has been disclosed for the first time, in which a N-doped carbon encapsulated Fe–FeO x material (Fe–FeO x @NC) is applied as a catalyst, and various quinazolines (25 examples, 62–99%) are synthesized. The iron nanoparticles wrapped by nitrogen-doped carbon layers in Fe–FeO x @NC with strong anti-poisoning ability is the main reason for the high performance in the reaction. This protocol offers several advantages including the use of air as an oxidant, water as a solvent, and recyclable iron as a catalyst and high atom and step economy.